A complete total-factor CO2 emissions efficiency measure and "203060 CO2 emissions targets" for Shandong Province, China. (1st August 2022) - Li, Shuangjie; Diao, Hongyu; Wang, Liming; Li, Li
Abstract: Improving efficiencies in CO2 emissions plays an important role in achieving carbon neutrality, but often overlooked in the planning and transformation of energy systems. Although data envelopment analysis (DEA) models are widely used for measuring efficiency, few papers have paid attention to whether the selected variables properly reflect the process of real-life production. This paper presents improvements to the existing input-output variable system of total-factor CO2 emissions efficiency (TFCEE). The underlying research uses a slacks-based measure (SBM) with undesirable outputs to evaluate industrial TFCEE in Shandong Province, China, during the period 2006–2017. Based on current potential for CO2 emissions abatement, a roadmap is proposed for the "203060 targets". We ascertained that the main engine of net zero CO2 emissions is efficiency improvement initially, shifting to structural adjustment by 2035. By 2037, carbon capture, utilization, and storage (CCUS) technologies are expected to be the second largest emission reducer, following structural adjustment. Based on a correct variable selection for CO2 emissions efficiency measurement and the exploration of a carbon emission reduction roadmap, this study provides both empirical evidence and policy implications for achieving carbon peak and carbon neutral targets in industrially developed regions such as Shandong Province. Graphical abstract: Image 1